Students Anxiety during the times of Covid-19 - Atrous , Houssem Eddine; Ais, Hamza (Milev Journal of Research and Studies, 2022)
This study aims at investigating the existence of mental health issues related to the recent Covid-19 pandemic, specifically anxiety issues among university students. We used an online questionnaire to investigate this phenomenon among students of Batna and Oum el Bouaghi universities. The significance of the study is shedding light on anxiety and finding potential solutions for it. We found that students suffer from anxiety mainly due to these factors: students’ uncertainty about their future study and career, social distancing, the economic state, and the fear of catching corona virus. Furthermore, we reached promising solutions that both the government and individuals can apply. We concluded that there is a need to raise awareness about the importance of mental health in Algeria, especially during and after the pandemic times.